Automated Detection Algorithm for SACZ, Oceanic SACZ, and Their Climatological Features - Rosa, Eliana Bertol; Pezzi, Luciano Ponzi; Quadro, Mario Francisco Leal de; Brunsell, Nathaniel (Frontiers in Environmental Science, 2020)
The South Atlantic Convergence Zone (SACZ) is responsible for a large amount of the total summer precipitation over Brazil and is related with severe droughts and extreme floods over the southeast of Brazil. This paper aims to demonstrate the feasibility of an objective, simplified and automated method based on satellite outgoing longwave radiation (OLR) for SACZ and oceanic SACZ (SACZOCN) detection to characterize their climatological features. SACZ dates and characteristics (intensity and size) detected by an automated algorithm have been made available for the first time in the literature. The method accurately detected 77% of SACZ occurrences compared with 21 years of SACZ observations. The temporal criterion of permanency of the SACZ convective activity for at least four days was essential to differentiate the SACZ from the transient frontal systems over the Brazilian Southeast. About 30% of the SACZ days occurred in November and March, therefore the December to February period is not sufficient to represent its activity. A barotropic through near the Uruguay coast determines the intensity and position of the coastal and oceanic SACZ portions. When this trough closes into a cyclonic vortex Southwest of the SACZ cloud band it characterizes an oceanic SACZ episode. SACZOCN episodes were objectively identified for the first time in the literature, being characterized by a more intense and northward displaced convective activity. We show that some oceanic SACZ episodes are associated with extreme floods and severe droughts over Brazil, therefore its identification is extremely important to the Brazilian society. In addition, oceanic surface currents and temperature over the Southwestern Atlantic Ocean are modified during the SACZOCN active phase. The method presented here is a viable alternative to objectively classify SACZ and SACZOCN episodes, it can be implemented operationally and used to SACZ studies in the context of climate change.